Increased risk of modality failure with higher serum uric acid level in continuous ambulatory peritoneal dialysis patients: a prospective cohort study. Issue 1 (31st December 2022) - He, Shuiqing; Xiong, Qianqian; Li, Li; Lin, Xuechun; Zhao, Jing; Guo, Xiaolei; He, Yuqin; Liang, Wangqun; Ying, Chenjiang; Zuo, Xuezhi
Abstract: Background: Peritoneal dialysis (PD) is one of the most important kidney replacement therapies for patients with end‐stage kidney disease (ESKD). PD technique failure can lead to an escalated cost and increased infectious and cardiovascular risk, up and including to death. The accumulation of uric acid (UA) was associated with adverse outcomes in ESKD patients. However, the relationship between serum UA and technique failure is little explored. Methods: Here, a total of 266 continuous ambulatory peritoneal dialysis (CAPD) patients (age, 41.8 ± 12.6 years; 125 males) were enrolled and followed up for 31.7 months. Serum UA levels were examined at baseline and each visit. Subjects were divided into three groups according to their baseline serum UA concentrations. Multivariable Cox regression models were used to estimate the hazard ratios (HRs) and 95% confidence intervals (CIs) of PD technique failure. Results: The level of serum UA increased gradually as time prolonged. During the follow-up period, 77 (28.9%) patients occurred PD technique failure, of which 56 (21.1%) transferred to hemodialysis (HD) and 21 (7.9%) died. Compared to the lowest UA tertile, after adjusting for potential confounders, HRs of technique failure in tertile 2 and tertile 3 were 1.82 (95% CI: 0.95–3.49) and 2.03 (95% CI: 1.05–3.92), respectively, and p for trend was 0.043. Adjusted HRs of all-cause technique failure, transferring to HD and mortality with each 1 mg/dL increase in serum UA were 1.20 (95% CI: 1.03–1.40, p = 0.019), 1.22 (95% CI: 1.01–1.48, p = 0.039), and 1.25 (95% CI: 0.94–1.67, p = 0.128), respectively. Conclusion: Higher serum UA level predicted higher risk of technique failure in CAPD patients.